Dental pulp as a source of low-contaminated DNA. (April 2017) - Drancourt, Michel; Aboudharam, Gérard; Croce, Olivier; Armougom, Fabrice; Robert, Catherine; Raoult, Didier
Abstract: The in-laboratory contamination of the ancient samples hinders the result interpretation of the investigations in the field of paleomicrobiology. We had promoted the dental pulp as a sample that limits the risks of in-laboratory contamination of the ancient material. In this work, we measured the contamination of the dental pulp manipulated according to paleomicrobiology protocol, used as a source of a total DNA for metagenomics. First, total DNA extracted from two dog canines was sequenced using next generation sequencing. This yielded a total of 487, 828 trimmed reads with a length of 227 ± 35 bp. Sequence analysis of the final dataset using Blast algorithm search and stringent thresholds for sequence identity and coverage against a database including both Canis lupus familiaris and Homo sapiens complete genomes showed that 95% of reads were assigned to C. familiaris whereas 0.03% was assigned to H. sapiens. In a second step, two teeth collected from two 12th century mammals were manipulated following the same protocol. A total of 13, 890 trimmed reads with a 157 ± 67 bp length yielded 0–0.35% reads assigned to H. sapiens . This study indicates that the dental pulp is a useful for detecting the significant nucleic sequences in both modern and ancient samples. Highlights: The dental pulp is almost free of in-laboratory contamination by modern DNA. Applying good laboratory practice to the dental pulp experiments limits the in-lab contamination of the samples. The dental pulp is a useful sample for detection of the significant nucleic sequences in both modern and ancient samples.